2017
DOI: 10.3390/s17040827
|View full text |Cite
|
Sign up to set email alerts
|

A Waist-Worn Inertial Measurement Unit for Long-Term Monitoring of Parkinson’s Disease Patients

Abstract: Inertial measurement units (IMUs) are devices used, among other fields, in health applications, since they are light, small and effective. More concretely, IMUs have been demonstrated to be useful in the monitoring of motor symptoms of Parkinson’s disease (PD). In this sense, most of previous works have attempted to assess PD symptoms in controlled environments or short tests. This paper presents the design of an IMU, called 9 × 3, that aims to assess PD symptoms, enabling the possibility to perform a map of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 43 publications
0
38
0
1
Order By: Relevance
“…In support of this, a recent report suggested that continuous gait monitoring detects higher step variability in PD patients with a positive history of falls compared to non-fallers [ 47 ]. Mobile wearable systems may have the potential to predict the patient’s risk of falling [ 48 ]. This may help facilitate the patient and physician to intervene and adjust treatment before falls occur.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a recent report suggested that continuous gait monitoring detects higher step variability in PD patients with a positive history of falls compared to non-fallers [ 47 ]. Mobile wearable systems may have the potential to predict the patient’s risk of falling [ 48 ]. This may help facilitate the patient and physician to intervene and adjust treatment before falls occur.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many undergoing projects are trying to implementing artificial intelligence algorithms for PD symptom-monitoring tasks inside non-intrusive wearable technologies. These systems aim to be suitable for daily addressing this monitoring task [33,34,35,36,37,38]. Within the same trend, state-of-the-art for automatic FOG detection are shallow machine learning (ML) algorithms applied to signals acquired from inertial measurement units (IMU) [39,40,41,35].…”
mentioning
confidence: 99%
“…The former has an increased power consumption, but a greater transmission speed and distance with respect to the latter. The sample frequency of these sensors varies between 50 and 1000 Hz while the minimum number of bit is 12 [ 106 ].…”
Section: Resultsmentioning
confidence: 99%